Reaching primary education at the doorstep of the poor: the BRAC experience - Nath, Samir Ranjan (BRAC Research and Evaluation Division (RED), 2019)
It is a review paper on BRAC education programme. Starting with a description of the country context of the initial days of the programme it describes how the programme was developed and implemented, and expended throughout the country using the gathered experiences. Impact of the programme, challenges faced and lesson learned were discussed afterwards.